Neonatal intramural calcification associated with jejunal atresia: a rare case report - Chakraborty, Goutam; Das, Sumanta; Sugandhi, Nidhi; Jadhav, Amit; Acharya, S.K.; Bagga, D (Tropical Journal of Pathology and Microbiology, 2019)
Neonatal intraabdominal calcifications are usually seen in conditions like intestinal atresia, meconium ileus and imperforate anus. It is mostly due to perforation of the obstructed proximal bowel followed by an inflammatory response of the matted loops and omentum, which initially is sterile to start with. Intramural calcification in intestinal atresia is a rare type of intra-abdominal calcification. The exact etiology of intramural calcification remains unclear, though ischemia secondary to any antenatal vascular insult like intussusception or volvulus is believed to be the triggering event. Intraperitoneal and intraluminal bowel calcification is generally visible on plain abdominal radiographs. Contrastingly, intramural calcification is by and large a histopathological finding. A 2-day old newborn male baby presented with signs of intestinal obstruction and was diagnosed to have jejunal atresia with meconium pseudocyst. The newborn underwent exploratory laparotomy with resection of the meconium pseudocyst and atretic and dilated part of the small bowel with jejunoileal anastomosis. Histology of dilated and atretic part of jejunum and adjacent area revealed intramural calcification.